1999
DOI: 10.1021/bi9913395
|View full text |Cite
|
Sign up to set email alerts
|

Rhodamine 110-Linked Amino Acids and Peptides as Substrates To Measure Caspase Activity upon Apoptosis Induction in Intact Cells

Abstract: Caspases (cysteine aspartate-specific proteases) are a structurally related group of cysteine proteases that cleave peptide bonds following specific recognition sequences. They play a central role in activating apoptosis of vertebrate cells. To measure apoptosis induced by various stimuli and at an early apoptotic stage, caspases are an ideal target. This is especially the case when apoptotic cells have to be analyzed ex vivo before phagocytes remove them. A new and sensitive caspase assay is based on a substr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
79
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(81 citation statements)
references
References 22 publications
1
79
0
1
Order By: Relevance
“…The most recent findings of caspase activity in the marine cyanobacterium Trichodesmium spp. (Berman-Frank et al, 2004) prompted our investigation to utilize caspase activity as a proxy for PCD in M. aeruginosa (Hug et al, 1999, Liu et al, 1999. We demonstrated that caspase activity in stressed M. aeruginosa cells might be responsible for the onset of PCD when induced with H 2 O 2 as a result of oxidative stress (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The most recent findings of caspase activity in the marine cyanobacterium Trichodesmium spp. (Berman-Frank et al, 2004) prompted our investigation to utilize caspase activity as a proxy for PCD in M. aeruginosa (Hug et al, 1999, Liu et al, 1999. We demonstrated that caspase activity in stressed M. aeruginosa cells might be responsible for the onset of PCD when induced with H 2 O 2 as a result of oxidative stress (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Cells, after 48 h of incubation were rinsed with PBS and incubated with 5 μg/ml D 2 R for 10 min at 37˚C. D 2 R is a non-fluorescent substrate for caspases and is intracellularly cleaved to rhodamine 110 (17). The fluorescence was measured with a confocal microscope Olympus FV500.…”
Section: Methodsmentioning
confidence: 99%
“…To determine caspase-1 activity in intact monocytes, a method described by Hug et al (8) was adapted. PBMC were stimulated with 10 g/ml LPS at 37 or 40°C.…”
Section: Measurement Of Caspase-1 Activity In Monocytesmentioning
confidence: 99%